Characterization and evaluation of acid-modified starch of Dioscorea oppositifolia (Chinese yam) as a binder in chloroquine phosphate tablets (2013)
Chinese yam (Dioscorea oppositifolia) starch modified by acid hydrolysis was characterized and compared with native starch as a binder in chloroquine phosphate tablet formulations. The physicochemical and compressional properties (using density measurements and the Heckel and Kawakita equations) of modified Chinese yam starch were determined, and its quantitative effects as a binder on the mechanical and release properties of chloroquine phosphate were analyzed using a 23 full factorial design. The nature (X1), concentration of starch (X2) and packing fraction (X3) were taken as independent variables and the crushing strength–friability ratio (CSFR), disintegration time (DT) and dissolution time (t80) as dependent variables. Acid-modified Chinese yam starch showed a marked reduction (p<0.05) in amylose content and viscosity but increased swelling and water-binding properties. The modified starch had a faster onset and greater amount of plastic flow. Changing the binder from native to acid-modified form led to significant increases (p<0.05) in CSFR and DT but a decrease in t80. An increase in binder concentration and packing fraction gave similar results for CSFR and DT only. These results suggest that acid-modified Chinese yam starches may be useful as tablet binders when high bond strength and fast dissolution are required.